Selective electrochemical oxidative coupling of methane mediated by Sr2Fe1.5Mo0.5O6-δ and its chemical stability - Kannan P. Ramaiyan (Nature Portfolio, 2021)
Catalytic conversion of methane to ethene is limited by poor conversion, selectivity, and catalyst stability. Here a solid oxide electrolysis process is reported as a promising method for selective, partial oxidation of methane with low overpotentials.